(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
The rise of right-wing populism in recent years can be interpreted as a direct consequence of the crisis in the relationship between traditional parties and the civilian population. A careful reflection on this phenomenon, though, requires a more extensive and ramified explanation of its material and ideological causes. A significant role has also been played by the inability of the media and institutions to understand the needs of less well-to-do classes, driven, as they are, to search for alternatives in right-wing populism. This is accompanied by the structural crisis within the traditional left-wing political parties and their movements. They were unable to respond in a credible way to the devastating socio-economic effects of the 2008 global crisis and are now unable to restore a balance between welfare and development at a time when financial capital is volatile. These considerations are then augmented by a series of comparisons between the many forms that populism has taken both in the western world and beyond, in particular comparisons between protectionist populism in the United States, nationalism in Turkey and Hindu extremism in India. Taking these differences into account, today’s populism seems to have originated in the cyclical worsening of popular resentment and in the weakening of social democratic bonds between social classes. These tensions can only be countered by politics that are more human and attentive to the actual needs of the civilian population.